Evaluation of the Pesawaran Regency Government Website Using the Method Usability Testing - Arif Prayoga; Iran Ferli; M Ulil Absor; M Shalahuddin Al Ayyubi (Proceeding International Conference on Information Technology and Business, 2021)
The Development of information and communication technology plays an important role in the implementation of e-government. The goal is that governance involving government, the private sector and society can be created in such a way that it is effective, efficient, productive and responsive. Pesawaran regency is one of the regencies in Lampung Province that has implemented e-government throughthe website, with the address pesawarankab.go.id. This research draws on the Website Usability Evaluatio (WEBUSE) approach to evaluating usability on the website of the Pesawaran Regency Government with dimensions of Content, Organization and Readability, Navigation and Links, User Interface Design andPerformance and Effectiveness. Website Usability Evaluation (WEBUSE) focuses on developing a webbased usability evaluation system with a subjective action approach involving user participation to provide an assessment of a website. The development of the Website Usability Evaluation (WEBUSE) approach as a standard usability measurement, with a web-based questionnaire evaluation method that allows users to assess the usability of the website to be evaluated. The purpose of this research is to find out the level of Usability of the Pesawaran Regency Government website can provide optimal service to users.Keywords—evaluation, website, webuse, pesawaranregency